SOSIALISASI DAN REHABILITASI MANGROVE DI DESA WAIHERU KECAMATAN TELUK AMBON BAGUALA KOTA AMBON GUGUS PULAU VII - Aniesa Nabila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2021)
Community service activities aim to rehabilitate the mangrove ecosystem in Waiheru Village. The solutions offered include: (1). Social approach with the Government and the community, (2). Carry out counseling, lectures and questions and answers about various knowledge about the role and importance of mangrove ecosystems for the environment and society. In addition, mangrove rehabilitation was carried out in collaboration with the Waiheru village community and the Maritime Affairs and Fisheries Service of Maluku Province. Mangrove planting of 200 seedlings is expected to grow successfully in the future. This requires very large participation from the Waiheru village community to carry out post-coaching guidance so that there are no disturbances from outside factors. The conclusion from the community service activities is the planting of 200 mangrove saplings to rehabilitate some of the damaged mangrove areas.